2005
DOI: 10.1016/j.ymthe.2004.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Liver-directed neonatal gene therapy prevents cardiac, bone, ear, and eye disease in mucopolysaccharidosis I mice

Abstract: Mucopolysaccharidosis I (MPS I) due to deficient alpha-L-iduronidase (IDUA) activity results in accumulation of glycosaminoglycans in many cells. Gene therapy could program liver to secrete enzyme with mannose 6-phosphate (M6P), and enzyme in blood could be taken up by other cells via the M6P receptor. Newborn MPS I mice were injected with 10(9) (high dose) or 10(8) (low dose) transducing units/kg of a retroviral vector (RV) expressing canine IDUA. Most animals achieved stable expression of IDUA in serum at 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 41 publications
5
92
1
Order By: Relevance
“…Using either adenoassociated virus [21] or lentiviral vector [23] to deliver therapeutic IDUA genes to newborn mice, persistent high-level IDUA expression over several months was observed in the liver, heart, lung and brain with subsequent curative impact on several of the most important parameters of the disease, including reduced storage vacuoles in a number of tissues, reduced glycosaminoglycan excretion, prevention of craniofacial abnormalities and behavioral abnormalities. Using a single injection of retroviral vector in neonates Liu et al [24] demonstrated sustained supra-normal IDUA expression in the liver throughout an 8-month experiment which resulted in prevention of major clinical manifestations of MPS I including cardiac and bone disease, hearing loss and vision abnormalities. The latter study demonstrated the effectiveness of targeting hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using either adenoassociated virus [21] or lentiviral vector [23] to deliver therapeutic IDUA genes to newborn mice, persistent high-level IDUA expression over several months was observed in the liver, heart, lung and brain with subsequent curative impact on several of the most important parameters of the disease, including reduced storage vacuoles in a number of tissues, reduced glycosaminoglycan excretion, prevention of craniofacial abnormalities and behavioral abnormalities. Using a single injection of retroviral vector in neonates Liu et al [24] demonstrated sustained supra-normal IDUA expression in the liver throughout an 8-month experiment which resulted in prevention of major clinical manifestations of MPS I including cardiac and bone disease, hearing loss and vision abnormalities. The latter study demonstrated the effectiveness of targeting hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…MPS I mice [19][20][21], deficient in α-L-iduronidase (IDUA; EC 3.2.1.76), are a model for one of the most common MPS diseases in humans [22][23][24][25][26]. Here we show that the SB system can mediate prolonged expression of lysosomal enzymes to treat MPS disease.…”
Section: Introductionmentioning
confidence: 94%
“…MPS I mice [23] were on a C57BL/6 background and normal controls were heterozygous littermates. Some MPS I mice were injected IV with 10 10 transducing unit (U) U/kg of the retroviral vector hAAT-cIDUA-WPRE at 2-3 days after birth [7]. For compliance curves, periadventitial fat was removed from ascending aortas and the outer diameters determined halfway between the sinotubular junction and the innominate artery [23].…”
Section: Methodsmentioning
confidence: 99%
“…Pathology-Ascending aortas were fixed as described [7] and a region 3 mm from the aortic valve was obtained. Six micrometer sections were stained with Verhoeff's Van Gieson (VVG) stain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation